ANXIETY, COPING MECHANISM, AND INTRAPSYCHIC CONFLICT PORTRAYED IN HANYA YANAGIHARA’S A LITTLE LIFE - Haliza Sabrina; Margawati, Prayudias (English Literature Department, Faculty of Economics, Law, and Humanities, 2024)
A Little Life by Hanya Yanagihara is an adult friendship novel that explores the traumatized condition cantered on the protagonist during his childhood which left him with a mental disorder called anxiety. This study aims to explore the anxiety disorder as the impact of childhood trauma experienced by the main character. The objective of this study is to examine the cause of anxiety disorder, coping mechanism towards main character’s anxiety, as well as the intrapsychic conflict caused by character’s neurotic condition by applying Karen Horney’s theory of basic hostility and basic anxiety. This study uses descriptive qualitative research methods. The results of this study indicate the main character suffers basic hostility and basic anxiety caused by childhood trauma abuse. The basic anxiety identified due to the main character was sexually abused during his childhood. In a way to cope with his anxiety condition, the main character depicted Detached (Move Away from People) type of neurotic trends as proposed by Karen Horney. Hereafter, the neurotic condition experienced by the main character leave him with an intrapsychic conflict that leads to a self-hatred image which is manifested in the form of self-destructive behaviours including self-harm, being a workaholic, and also suicide thoughts and attempts.